Development and trafficking function of haematopoietic stem cells and myeloid cells during fetal ontogeny. (18th May 2015) - Heinig, Kristina; Sage, Fanny; Robin, Catherine; Sperandio, Markus
Abstract: Fetal haematopoiesis is a highly regulated process in terms of time and location. It is characterized by the emergence of specific cell populations at different extra- and intraembryonic anatomical sites. Trafficking of haematopoietic stem cells (HSCs) between these supportive niches is regulated by a set of molecules, i.e. integrins and chemokine receptors, which are also described for the recruitment of differentiated innate immune cells. In this review, an overview will be given on fetal haematopoiesis as well as trafficking of HSCs during fetal life. In addition, we will focus on the appearance of the first differentiated neutrophils and monocytes in the fetal circulation and describe how they acquire the ability to roll, adhere, and transmigrate into inflamed fetal tissue. Furthermore, we will discuss other effector functions of innate immune cells evolving during fetal ontogeny.